Description of ventilator-associated pneumonia - González Baños, Yanara; Terrado Almarales, Osiris Oscar; Rego Avila, Heidy (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Pneumonia associated with mechanical ventilation constitutes one of the main infections associated with health services and the main complication of mechanical ventilation. The present investigation was developed with the aim of describing ventilator-associated pneumonia. A literature review was carried out in the Scopus, SciELO and Redalyc databases, obtaining 37 references.  This entity is an infection of the lower airway that produces an acute inflammatory lesion of the pulmonary parenchyma that occurs in response to the arrival of the microorganism to the distal airway, and which is acquired in the hospital 48 hours after endotracheal intubation. The symptoms and signs may manifest as the presentation of a series of symptoms and signs, either progressive or abrupt, such as dyspnea, fever, tachypnea, purulent expectoration, hemoptysis, rhonchi, crackles, hypoventilation and bronchospasm. Diagnosis is clinical, radiological and laboratory.